-3w+11=-8w+51

Simple and best practice solution for -3w+11=-8w+51 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3w+11=-8w+51 equation:


Simplifying
-3w + 11 = -8w + 51

Reorder the terms:
11 + -3w = -8w + 51

Reorder the terms:
11 + -3w = 51 + -8w

Solving
11 + -3w = 51 + -8w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '8w' to each side of the equation.
11 + -3w + 8w = 51 + -8w + 8w

Combine like terms: -3w + 8w = 5w
11 + 5w = 51 + -8w + 8w

Combine like terms: -8w + 8w = 0
11 + 5w = 51 + 0
11 + 5w = 51

Add '-11' to each side of the equation.
11 + -11 + 5w = 51 + -11

Combine like terms: 11 + -11 = 0
0 + 5w = 51 + -11
5w = 51 + -11

Combine like terms: 51 + -11 = 40
5w = 40

Divide each side by '5'.
w = 8

Simplifying
w = 8

See similar equations:

| y=7x^2-4x | | 7x-5y-10=0 | | 24=-11y-8+3y | | 60*0.2= | | 3w-4=-16 | | -32=w/5-7 | | -v+131=180 | | 31=-u+184 | | 205=96-y | | -25=4u+3 | | 82-(4-6)2= | | 25n^8-49n^7-2n^6=0 | | -3+w=-4 | | -6=u-4 | | 5(2x-9)+3x=4x-18 | | 13=0.5((4x-10)+(3x+8)) | | 9x-(x+4)=2x+32 | | (1/7(x))+((1/7)x+1)+29=x | | 2x^1/2-7x^1/4+3=0 | | 63=.5h*9 | | 4x+7=54 | | 1/2*(3/5((2^3)-6))+1/5 | | 7/5x^2-7/9x-4/3x | | 1/2*3/5((2^3)-6)+1/5 | | 82x+4x=68.5 | | 5y+1/9=6y+5/9 | | 0.50x+0.05(80)=0.25(64) | | -8(x+5)+3=-37 | | 5x/14-3x/14-11x/14= | | -3x+2y+z=4 | | (3x+2)(5x-1)= | | (x-74)/x=0.4 |

Equations solver categories